The Role of Natural Language Processing (NLP) in Advancing Language Learning Technology in Educational Platforms - Loso Judijanto (Edujavare Publishing, 2023)
This research explores the role of Natural Language Processing (NLP) in enhancing language learning technologies within educational platforms. With the increasing reliance on digital tools for language education, NLP technologies offer promising solutions for personalizing learning, providing real-time feedback, and improving learner engagement. The study aims to investigate how NLP is applied in language learning platforms, identify its benefits and challenges, and explore its potential for further development. Using a qualitative approach, the research includes case studies of popular language learning platforms such as Duolingo and Babbel, and interviews with educators, language learners, and platform developers. Thematic analysis was employed to examine the data, identifying key themes such as personalized learning, learner engagement, and conversational simulation. The findings indicate that NLP significantly enhances personalized learning experiences by adapting content to individual learner needs and providing immediate feedback, which improves learner retention and motivation. However, challenges related to the system's ability to capture linguistic nuances and regional variations, as well as concerns about data privacy, were also identified. This study concludes that while NLP has great potential to transform language education, there are still limitations that need to be addressed. Future research should focus on refining NLP algorithms to handle complex language structures and cultural contexts, as well as addressing ethical concerns regarding data security. The study contributes valuable insights for educators, developers, and policymakers looking to integrate NLP into language learning platforms.